2022
DOI: 10.1097/sle.0000000000001098
|View full text |Cite
|
Sign up to set email alerts
|

Two Decades’ Outcomes and Trends of Adrenalectomy for Benign Pathologies in Veterans

Abstract: Background: Since the introduction of laparoscopic adrenalectomy (LA) in 1992, it has become the standard of care for most adrenal benign pathologies. This study compares the outcomes and trends of open (OA) versus LA in veterans for benign pathologies.Methods: Veterans Affairs Surgical Quality Improvement Program was queried for adrenalectomies performed for benign pathologies during the period 2000-2019. Data collection included demographics, comorbidities, operative details, and postoperative outcomes.Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…The benefits of the minimally-invasive approach were proved in many previous works. In their study of 1683 adrenalectomy patients, Shahait et al showed that laparoscopic adrenalectomy was associated with lower morbidity and mortality, shorter length of stay, and less blood loss compared with the open approach [14]. In their retrospective analysis, Mohammed et al proved that there is no priority of the open approach in adrenal tumors that are 5 cm or larger concerning complication rate, length of stay, mortality, or oncologic outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The benefits of the minimally-invasive approach were proved in many previous works. In their study of 1683 adrenalectomy patients, Shahait et al showed that laparoscopic adrenalectomy was associated with lower morbidity and mortality, shorter length of stay, and less blood loss compared with the open approach [14]. In their retrospective analysis, Mohammed et al proved that there is no priority of the open approach in adrenal tumors that are 5 cm or larger concerning complication rate, length of stay, mortality, or oncologic outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Robotic-assisted resection was also recommended in more difficult cases or larger tumors, as it may provide the needed dexterity for handling such tumors [16]. Therefore, it is no wonder that the use of minimally invasive adrenalectomy is on the rise, with trend analysis showing an increase of eight-fold over a period of 20 years [14].…”
Section: Discussionmentioning
confidence: 99%
“…The rate of performed adrenalectomies has been increasing with the increased adoption of minimally invasive surgical approaches and the widespread utilization of cross-sectional images [1][2][3]. A recent study using the Veterans Affairs Surgical Quality Improvement Program found that the rate of laparoscopic adrenalectomy has increased eight-fold over the last 20 years [2]. Not only has the rate of performed adrenalectomies continued to raise, but also the rate of implementing minimally invasive techniques in adrenal surgery.…”
Section: Introductionmentioning
confidence: 99%